Strategi Value Seeking dan Stock Piling: Respons Konsumen terhadap Kenaikan PPN 12% pada Produk Non-Esensial - Wahyu Leman; Dedi Muliadi (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2026)
The increase in the Value Added Tax (VAT) rate to 12% on non-essential products has the potential to affect people's consumption behavior. The change in fiscal policy encourages consumers to adjust their purchasing strategies to maintain the expected level of utility. This study aims to analyze consumer responses to the 12% VAT increase by focusing on value seeking and stock picking strategies, and examine the influence of these two strategies on changes in consumption behavior of non-essential products. This study uses a quantitative approach with a survey method of 100 respondents who are consumers of non-essential products. Data were collected through a structured questionnaire that had met the validity and reliability tests, then analyzed using inferential statistical tests in the form of t-tests and F-tests. The results of the analysis showed that partially the value seeking strategy had a positive and significant effect on consumer response, with a t-table value of > and a significance level of < 0.05. This strategy is reflected in the increasing consumer behavior in comparing prices, looking for discounts, and choosing alternative products that have a higher benefit value· The stock piling strategy also shows a significant influence on consumer response, although its contribution is relatively smaller than that of value seeking. Simultaneous testing through the F test showed that the two independent variables together had a significant effect on consumer response to the 12% increase in VAT, with a Fcal value of > Ftable and a significance of < 0.05. The value of the determination coefficient (R²) indicates that the proportion of variation in consumer responses can be explained moderately by both strategies. These findings show that consumers are adaptive and rational in the face of VAT increase policies, not only by reducing consumption, but through adjustments to purchasing strategies. This research provides a theoretical contribution to the study of consumer behavior and practical implications for policymakers and business actors in responding to changes in fiscal policy.